2001
DOI: 10.1016/s0033-3549(04)50018-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative accuracy of clinical estimate versus menstrual gestational age in computerized birth certificates

Abstract: Agreement between menstrual and clinical estimates of gestational age occurs most often close to term, with significant disagreement in preterm and postterm births. Use of different methods of determining gestation in different years or geographic populations will result in artifactual differences in important indicators such as prematurity rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…33 However, if this information is underreported on the birth certificate, our results are conservative estimates of the true effect of these variables on the risk of infant death. Similarly, gestational age is reported less accurately than birth weight on the birth certificate, 8,34 and this difference in reporting accuracy could have affected our comparisons of the risk of low birth weight and prematurity on infant death. Finally, vital records data sets do not contain information about factors such as quality of prenatal care, quality of neonatal and postneonatal care, and community or environmental factors, any of which may affect the risk of infant death.…”
Section: Discussionmentioning
confidence: 99%
“…33 However, if this information is underreported on the birth certificate, our results are conservative estimates of the true effect of these variables on the risk of infant death. Similarly, gestational age is reported less accurately than birth weight on the birth certificate, 8,34 and this difference in reporting accuracy could have affected our comparisons of the risk of low birth weight and prematurity on infant death. Finally, vital records data sets do not contain information about factors such as quality of prenatal care, quality of neonatal and postneonatal care, and community or environmental factors, any of which may affect the risk of infant death.…”
Section: Discussionmentioning
confidence: 99%
“…The deficiencies of LMP-based gestational age are well established. [20][21][22][23] Recently, Qin et al 24 used a simple method in which the CE of gestational age is substituted for LMP-based gestational age when the difference between the two estimates is greater than 2 weeks (LMP/CE method). They demonstrated that the LMP/CE method, when compared with other techniques, almost eliminated the second mode in the gestational age distribution.…”
Section: Methodsmentioning
confidence: 99%
“…Gestational ages based on recall of last menstrual period (LMP), such as those employed here are often misestimated due to errors in recall, inter and intra individual variations in the menstrual cycle, bleeding in early pregnancy, and unrecognized miscarriage (David, 1980;Kramer et al, 1988;Mustafa and David, 2001;Platt et al, 2001;Savitz et al, 2002;Todros et al, 1991). The clinical estimates of gestational age are not based on a consistent set of evidence and are similarly flawed (Alexander et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Most recent studies operationalize ''compromised'' births as small for gestational age (SGA) (Forbes and Smalls, 1983;Goldenberg et al, 1989;Lubchenco et al, 1963), or as low fetal growth ratio (LFGR) (Kramer et al, 1989;Steward and Moser, 2004), or both (Frisbie et al, 1996). These methods have been criticized, (a) because they all require ad hoc cut points to define the categories (Alshimmiri et al, 2003;Hellier and Goldstein, 1979;Kohn et al, 2000;Madani et al, 1995;Van der Veen, 1998;Yerushalmy, 1967), and (b) because gestational age is often poorly estimated (Alexander et al, 1995;David, 1980;Kramer et al, 1988;Mustafa and David, 2001;Platt et al, 2001;Savitz et al, 2002;Todros et al, 1991). Nevertheless, both birth weight and gestational age are considered to have an independent influence on birth outcomes and the majority of research in the last several decades has used both variables.…”
mentioning
confidence: 99%